Chromosome Breakage Induced by the Genotoxic Agents Mitomycin C and Cytosine arabinoside - Gareth Jenkins (Toxicological Sciences, 2014)
The p53 tumor suppressor protein plays an essential role in cellularintegrity and inactivation of the TP53 gene by mutation isthe most frequent alteration in human cancer. As loss of p53 functionis associated with increased genetic instability, it is importantin genotoxicity testing to explore the role of p53 competency. Invitro model systems for genotoxicity testing are sometimes prone tomisleading positive results; some of this loss of predictivity may becaused by p53 inactivation in some cellmodels. To explore whetherimpaired p53 function plays a role in mutation sensitivity, TK6cells (p53 competent) and NH32 cells (p53 deficient) were treatedwith two known genotoxicants, mitomycin C (MMC) and cytosinearabinoside (araC). Chromosomal damage was assessed in the lowdose region by an automatedmicronucleus system and p53 activitywas investigated by gene and protein expression analysis. Cell cycleprogression studies were also assessed. Low levels of micronucleusand p53 induction were observed in TK6 cells treated with MMC.On the other hand, higher levels of micronucleus and p53 inductionwere shown in TK6 cells treated with araC and a G1/S arrestwas observed after araC treatment. p53 deficient NH32 cellsshowed an increased sensitivity of micronucleus (MN) inductionafter araC treatment compared with TK6 cells and less of an activeG1/S phase checkpoint. Thus, impaired p53 function sensitizescells to genotoxicants and plays a central role in the DNA damageresponse. This data has clear importance for safety assessment ofgenotoxicity and shows how crucial p53 competence.